2019
DOI: 10.2147/hmer.s144667
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cognitive impairment after liver transplantation: residual hepatic encephalopathy or posttransplant encephalopathy?</p>

Abstract: Liver transplantation (LT) represents the definitive treatment for end-stage liver disease. Cognitive impairment following LT is frequent, referred to as postliver transplant encephalopathy (PLTE). LT removes the underlying chronic liver disease, and until recently hepatic encephalopathy (HE) was assumed to be fully reversible after LT. However, increasing evidence indicates that some degree of cognitive impairment may be present after LT. To which extent PLTE reflects cognitive impairment caused by residual H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Liver transplant research has suggested that multiple factors related to transplant, including unresolved pretransplant hepatic encephalopathy, comorbidities, and immunosuppressant treatment, may be etiologically associated with posttransplant cognitive impairment, in addition to aging of recipients. 11,12 This study found that male recipients demonstrated lower scores on tests of memory than female recipients. While the sex difference in cognitive function has not been reported in the liver transplant population, 2 this pattern of sex difference on memory is congruent with widely published studies on memory, which demonstrated that females have higher levels of memory than males.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Liver transplant research has suggested that multiple factors related to transplant, including unresolved pretransplant hepatic encephalopathy, comorbidities, and immunosuppressant treatment, may be etiologically associated with posttransplant cognitive impairment, in addition to aging of recipients. 11,12 This study found that male recipients demonstrated lower scores on tests of memory than female recipients. While the sex difference in cognitive function has not been reported in the liver transplant population, 2 this pattern of sex difference on memory is congruent with widely published studies on memory, which demonstrated that females have higher levels of memory than males.…”
Section: Discussionmentioning
confidence: 71%
“…There is a lack of knowledge regarding the demographic and clinical characteristics of liver transplant recipients with cognitive impairment. 11 Such data may provide clues as to who is at higher risk of developing cognitive impairment posttransplantation. Recipients over the age of 65 years in this study had lower scores in global cognitive function and visuospatial/ executive function than those under the age of 65.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretransplant hepatic encephalopathy and alcoholrelated liver diseases are key risk factors for posttransplant cognitive impairment. (3,29) Hepatic encephalopathy affects visuospatial abilities, attention, and psychomotor speed, (30) and alcohol-related liver diseases affect memory and executive function. (31) In line with previous findings, this study demonstrates poorer subjective cognition in domains affected by hepatic encephalopathy (eg, ECog visuospatial abilities, planning, and divided attention) in LT recipients with pretransplant hepatic encephalopathy than in those without the condition.…”
Section: Discussionmentioning
confidence: 99%
“…HE, especially OHE, has adverse effects on the quality of life, cognitive function, and working ability [ 3 4 ]. Although LT is the most effective strategy to restore cognitive function, it is still debated whether cognition can be fully reversed after LT [ 5 6 ]. Moreover, increasing evidence indicates that OHE may be an important factor for residual cognitive deficits after LT [ 2 7 ].…”
Section: Introductionmentioning
confidence: 99%